1998
DOI: 10.1046/j.1365-2133.1998.02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous metastasis from a presumed signet-ring cell carcinoma in a 10-year-old child

Abstract: Cutaneous metastases of internal malignancies are very rare in children. In this group, neuroblastoma, leukaemia and lymphoma are the most common malignancies that may develop metastases or neoplastic infiltrates to the skin. Carcinomas have infrequently been reported in children, and cutaneous metastases from carcinoma in this group have not been described. A 10-year-old girl presented with an erythematous plaque on the left hemithorax. Histopathological findings revealed grouped signet-ring cells within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Cutaneous metastasis of malignant neoplasms are generally uncommon, but are being diagnosed with increasing frequency in recent years. In about 3–10% of patients with malignant neoplasms develop cutaneous metastases 1 . Cutaneous metastasis from gastric carcinoma is rare and usually occurs in the later stages of the disease, as in our case.…”
supporting
confidence: 53%
“…Cutaneous metastasis of malignant neoplasms are generally uncommon, but are being diagnosed with increasing frequency in recent years. In about 3–10% of patients with malignant neoplasms develop cutaneous metastases 1 . Cutaneous metastasis from gastric carcinoma is rare and usually occurs in the later stages of the disease, as in our case.…”
supporting
confidence: 53%
“…19 The incidence of malignant wounds in children is extremely rare. 20 In their retrospective study of 4,020 cancer patients, Lookingbill et al found only two cases of malignant wounds in children. 16 Most authors suggested that the prognosis for patients with malignant wounds was grave and that life expectancy may be less than six months.…”
Section: Epidemiologymentioning
confidence: 99%
“…These cells, however, have been also detected in other neoplasms such as basal cell carcinoma, squamous cell carcinoma, melanoma, non‐Hodgkin's lymphoma and liposarcoma 5 . Several immunohistochemical studies such as cytokeratin, S‐100 protein, HMB‐45 and LCA may be useful to rule out the possibility of metastasis from epithelial, melanocytic and lymphoid tumour, respectively 4 . Although metastatic lesions sometimes reveal histologic features different from those of the primary lesion, in our patient, the immunohistochemical profiles and the clinical history of gastric cancer assisted in clarifying the diagnosis.…”
mentioning
confidence: 70%
“…The presence of signet ring cells in a skin biopsy has most commonly been associated with metastatic adenocarcinoma of the gastrointestinal tract 4 . These cells, however, have been also detected in other neoplasms such as basal cell carcinoma, squamous cell carcinoma, melanoma, non‐Hodgkin's lymphoma and liposarcoma 5 .…”
mentioning
confidence: 99%